Search for magnets with properties intermediate between Nd-Fe-B and Ferrite - Tozman, Pelin (School of Physics. Discipline of Physics, 2018)
The rare earth elements neodymium, samarium, terbium and dysprosium are predominantly mined in China (>95%) there wild prices fluctuations in 2011 as a result of Chinese government policies undermined confidence in the security of rare earth supplies. There is a need for a new magnet with little or no rare earth to fill the magnet gap between ferrite and Nd-Fe-B, to be used for intermediate energy applications. In this thesis, a novel magnet aimed at intermediate energy applications is investigated (100 (BH)max 200 kJ/m3). Two approaches are used in order to fill this gap which are (1) atomic substitutions in known uniaxial materials with high Curie temperature with a view to reducing materiels cost or improving process ability (2) finding a new compounds from Heusler family.
Keywords: Physics